Perceived Challenges of First-Year College Students in PATHFIT 1 (Physical Activities Towards Health and Fitness) in One Private Higher Education Institution in Lemery, Batangas - Razon, Remedios; Dela Peña, Chona; Landicho, Ericson; Orlina, Francis Nicolai; Mirano, Haidee; Panganiban, Jade; Canosa, Jamaica Maribeth; Bautista, Harren James; De Ramos, Lovelita; Hernandez, Lyra Crizelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceived challenges experienced by first-year college students in PATHFIT 1 at Lemery Colleges in Lemery, Batangas, focusing on student attitude, student practice, teachers’ planning, implementation and actions, participation in physical activities, and skill learning. Using a descriptive research design, the study involved 68 first-year college students selected from a total population of 81 through stratified purposive sampling. Data were gathered using a validated researcher-made questionnaire and analyzed using percentage, weighted mean, standard deviation, Cronbach’s alpha, t-test, and ANOVA. Findings showed that most respondents were female, enrolled in education-related programs, living in their own homes, and moderately active before college. The students experienced challenging levels in student attitude, student practice, participation in physical activities, and skill learning, with major concerns involving limited teamwork, lack of motivation, inadequate practice, insufficient feedback, unclear instruction, limited facilities, and weak connection between theory and practice. Sex and prior physical activity level did not significantly affect perceived challenges, while program enrolled and residential type showed significant differences in selected areas, particularly participation, skill learning, and teachers’ planning and implementation. The study concluded that PATHFIT 1 students encounter interconnected motivational, instructional, environmental, and skill-related challenges. It recommended the use of a developed learning module, structured assessment tools, engaging activities, timely feedback, improved facilities, digital learning resources, and teacher professional development. The study supports SDG 3, Good Health and Well-Being, and SDG 4, Quality Education, by promoting physical activity, inclusive learning, and student development. Its sustainability impact lies in strengthening public health, educational quality, and institutional support for more responsive physical education programs.